Bridging diversity in biology education: A case study on multicultural personality in a project-based practicum - Cahyani, Paramitha; Hariyatmi, Hariyatmi; Aryani, Ima; Faozi, Ekan; Rachmanisa , Ashari; Tamamah , Vina; Widianti , Tri (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Indonesia's multicultural landscape presents both opportunities and challenges for educational institutions in fostering inclusive learning environments. This mixed-method case study explores the experiences of Biology Education pre-service teachers at Universitas Muhammadiyah Surakarta (UMS), particularly within a Project-Based Practicum (PBP) in a Histology course. The research involved 43 students as participants. Data were collected using two instruments: a modified short-form Multicultural Personality Questionnaire (MPQ) and a semi-structured interview guide. Quantitative data from the MPQ were analyzed using descriptive statistics, while qualitative interview data were examined through thematic analysis. The findings reveal that UMS students demonstrate high levels of tolerance, cultural empathy, and collaboration skills, essential for navigating diverse educational settings. However, challenges such as language barriers and cultural nuances were observed, particularly among minority groups from various Javanese regions. The implementation of PBP proved effective in enhancing students' interaction, communication, and adaptability. These results underscore the importance of inclusive, project-based learning models in developing cross-cultural competence, emotional resilience, and open-mindedness in multicultural classrooms